Ecological consequences of urbanization in Afrotropical bird communities: present and future prospects - Danmallam, Bello A.; Ngila, Peggy M.; Iniunam, Iniunam A.; Kuria, Anthony; Tende, Talatu; Ngugi, Samuel; Njoroge, Peter; Jackson, Colin; Okoth, Basil; Ottosson, Ulf; Chaskda, Adams A.; Trevelyan, Rosie (Frontiers in Conservation Science, 2024)
IntroductionUrbanization, characterized by the rapid expansion of human settlements and development, greatly impacts biodiversity, especially where developments and human settlements are not guided by proper environmental consideration.MethodsWe used data collected through citizen science projects under the African Bird Atlas Project, based on standardized protocols to gather bird occurrence data. Species’ ecological traits, related to foraging behavior, habitat speciality, and body mass, were analyzed to assess functional richness and functional diversity (FD) represented by Rao’s quadratic entropy. Geospatial data, including the Global Human Settlement Layer and Human Modification Index (HMI), along with the probability of urban expansion up to 2030, were integrated to examine the impact of urbanization using Bayesian models.ResultsOur findings reveal a marked decline in taxonomic richness, diversity, and functional richness associated with increasing urbanization and human modification, with a similar pattern observed along the gradient from mostly uninhabited areas to cities. However, FD increased with urbanization from uninhabited areas to cities. The relationship between FD and HMI was nonlinear, showing an initial negative trend that became positive as HMI increased. This suggests a transition in bird communities, where generalist species thrive in urban environments, potentially replacing specialized species and leading to functional redundancy.DiscussionDespite the complex relationships observed, urbanization has a predominantly negative impact on the richness and diversity of Afrotropical bird communities. The decline in avian diversity and functional richness has important implications for ecosystem functions and services, crucial for biodiversity and human well-being. Our research provides valuable insights into the ecological impacts of urban expansion and emphasizes the importance of preserving natural habitats amidst growing urban landscapes.